2017
DOI: 10.1038/s41598-017-05314-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel STK1-targeted small-molecule as an “antibiotic resistance breaker” against multidrug-resistant Staphylococcus aureus

Abstract: Ser/Thr protein kinase (STK1) plays a critical role in cell wall biosynthesis of and drug resistance in methicillin-resistant Staphylococcus aureus (MRSA). MRSA strains lacking STK1 become susceptible to failing cephalosporins, such as Ceftriaxone and Cefotaxime. STK1, despite being nonessential protein for MRSA survival, it can serve as an important therapeutic agent for combination therapy. Here, we report a novel small molecule quinazoline compound, Inh2-B1, which specifically inhibits STK1 activity by dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 72 publications
3
38
0
1
Order By: Relevance
“…Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 77%
See 3 more Smart Citations
“…Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 77%
“…Similarly, several studies have identified Stk1-inhibiting molecules from small-molecule libraries that sensitize MRSA S. aureus strains to b-lactams [223,[238][239][240]. Notably, Kant et al optimized a quinazoline-based Stk1-inhibiting molecule (Inh2-B1) that potentiates the bactericidal activity of the cephalosporins ceftriaxone and cefotaxime on drug-resistant S. aureus, both in vitro and in an in vivo septicemia mouse model with negligible cytotoxic side effects [240]. Mechanistically, Inh2-B1 was shown to reduce the expression of cell wall hydrolase-encoding genes important for cell wall synthesis and biofilm formation.…”
Section: Drugging Bacterial Kinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pentaglycine-lipid II interacts with the extracellular PASTA (penicillin binding protein and serine/threonine kinase associated) domains of Stk and triggers its kinase activity in vitro 9 . In fact, deletion of stp and stk in S. aureus causes cell division defects resulting in the formation of multiple and incomplete septa, differences in cell size and cell wall thickness 10 , 22 . In addition, stk and stk/stp deletion strains are more susceptible to cell wall-acting antibiotics like tunicamycin 12 , fosfomycin 12 , 20 and β-lactam antibiotics 10 , 16 .…”
Section: Introductionmentioning
confidence: 99%